2009
DOI: 10.1111/j.1468-3083.2008.02881.x
|View full text |Cite
|
Sign up to set email alerts
|

Urticariform striae distensae

Abstract: Fig. 1b). Interstitial mucins deposition was found in the superficial dermis. Calcification was observed in the deep dermis. A diagnosis of NSF was made. The skin lesions persisted till the patient succumbed to cancer metastasis.Only few cases of NSF were reported in patients who had ARF and never requiring dialysis. 2 Our case is unique because NSF occurred after renal function had returned to normal. The exact cause of NSF remained not clear. However, there was a very strong association between NSF and expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In the formation of striae distensae caused by steroids and glucocorticoids there is an imbalance of connective tissue and/or the dermal matrix due to the catabolic effect on fibroblast activity and decreasing collagen deposition in the dermal matrix [8], [19]. In an in vitro study conducted by Soares et al and Stipcevic et al administration of flavonoids in fibroblast culture, obtained a significant increase in collagen synthesis compared to placebo [11], [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the formation of striae distensae caused by steroids and glucocorticoids there is an imbalance of connective tissue and/or the dermal matrix due to the catabolic effect on fibroblast activity and decreasing collagen deposition in the dermal matrix [8], [19]. In an in vitro study conducted by Soares et al and Stipcevic et al administration of flavonoids in fibroblast culture, obtained a significant increase in collagen synthesis compared to placebo [11], [12].…”
Section: Discussionmentioning
confidence: 99%
“…Striae occur in skin areas with crosslinks of collagen fibers and immature elastic fibers which causes a limited degree of stretching and partial intradermal rupture. 16 Stretch and striae are a continuous process and adaptation to the growing need in adolescence, which changes body mass in early adulthood. Pieraggi et al showed that striae resulted from the disruption of elastic fibers due to tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic changes are found in striae such as fragmented collagen, an abundance of essential substances, and globular fibroblasts that lose all fibril secretion signs indicating fibroblast dysfunction due to distension. 16 Some supporting factors have been put forward besides physical growth include genetic, hormonal, and pathological disease processes. 16 The emergence of striae on the skin has been associated with a tendency to decrease families' disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations